Small rocky outcrops: natural features to promote biodiversity in oak wood‐pastures - Chozas, Sergio (2023)
Aims The Iberian oak wood-pastures are unique agroforestry systems supporting high levels of biodiversity and ecosystem services. Small rocky outcrops are geological features commonly found in these systems and constitute biodiversity reservoirs, protecting sensitive species from grazing and farming activities. We aimed to assess the relevance of including rocky outcrop conservation within wood-pastures to increase biodiversity. To achieve this goal, we study the plant communities occurring within the outcrops and in the wood-pasture matrix to evaluate the impact of rocky outcrops on the overall plant taxonomic and functional diversities of these systems. Location Montemor-o-Novo (Alentejo, Portugal). Methods We sampled 102 plant communities occurring in outcrops and in the adjacent wood-pasture matrix and analysed alpha, beta, gamma and functional diversities. We identified the main intrinsic factors affecting outcrop plant composition and their functional groups using Linear (LM) and Generalised Linear Mixed Models (GLMMs) and characterised the effect of outcrop size throughout Generalised Additive Models (GAMs). Results We found plant richness to be similar in wood-pasture matrix and outcrops. However, beta diversity analysis revealed a high species turnover between both communities. Functional indices indicated a higher plant functional diversity in outcrops and trait analyses identified three functional groups dissimilarly distributed in both communities: i) perturbation and stress-sensitive plants, with outcrops constituting an important refuge for this group, and ii) grazing-tolerant and iii) weedy herbs dominating the wood-pastures. Finally, we also found increased plant richness in outcrops with a higher length of their minor axis, i.e. wider outcrops, and higher rock cover area. Conclusions Our results indicate that the presence of small rocky outcrops in evergreen oak wood-pastures highly increase their gamma and functional diversities. Consequently, outcrop protection strongly impacts overall wood-pasture biodiversity and underline the suitability of including outcrop conservation as a cost-effective solution capable of increasing biodiversity in these agroforestry systems.